Efect of feeding Pleurotus pulmonarius‑treated empty fruit bunch on nutrient digestibility and milk fatty acid profles in goats - Mohamad Zaihan Zailan; Suraya Mohamad Salleh; Sumaiyah Abdullah; Halimatun Yaakub (Springer, 2023)
This study aimed to evaluate the efect of feeding P. pulmonarius-treated empty fruit bunch (FTEFB) on the nutrient intakes, digestibility, milk yield and milk profles of lactating Saanen goats. A total of nine lactating Saanen goats were used in an incomplete cross-over experimental design. The balanced dietary treatments contain diferent replacement levels of Napier grass with FTEFB at 0% (0-FT), 25% (25-FT) and 50% (50-FT). The FTEFB contained crude protein (CP), neutral detergent fbre (NDF), acid detergent fbre (ADF) and acid detergent lignin (ADL) at 4.10, 94.6, 70.8 and 19.4% DM, respectively. The replacement of FTEFB in 25-FT did not alter dry matter, NDF, hemicellulose, ADL, ether extract and gross energy intakes when compared to the control fed group (0-FT). The ADF and cellulose intake was higher in 25-FT than in the others (P<0.001). The digestibility of hemicellulose, cellulose and ADL were not changed in 25-FT compared to the control group (P<0.05) whereas when 50% FTEFB was incorporated to the diet, intermediate digestibility was decreased signifcantly (P<0.05). Milk yield and protein content did not difer between the goat received 25-FT and the control group (P>0.05). There are no diferences in milk fatty profles between dietary treatments (P>0.05), except for OCFA. Goat fed with 25-FT had the lowest OCFA (P<0.01) and signifcantly reduced the lauric acid concentration (P<0 .05) when compared to the control group. Thus, replacement of NG in 25-FT does not adversely afect nutrient intake, fbre digestibility (cellulose and hemicellulose), milk yield, milk composition and milk fatty acid profles. Overall, FTEFB may have potential to be used in the dairy goat diet as a roughage source to replace Napier grass.